Wujud Sikap Kerjasama Siswa pada Pembelajaran Seni Montase di Sekolah Dasar - Ema Rosilia; Putri Aprillia; Dewi Sulistyowati (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this research is to find out the form of cooperation attitude in montage art activities. This type of research is qualitative research. This research was conducted at SDN Karangrejo, Jakenan District, Pati Regency, Central Java Province on Saturday, 11 November 2023. The data collection techniques used in this study were observation, interview, and documentation. The informants in the data collection article are class IV students. Qualitative data analysis is inductive analysis, namely analysis based on data obtained during data collection. In other words, researchers use descriptive analysis techniques. Data analysis techniques in this study include: (1) Data collection from observations and interviews (2) Data reduction (data reduction) (3) Data verification (conclusion drawing/verification) drawing conclusions. The results of this study are the activities of montage art work there is a form of student cooperation during the process of making montage artworks including when dividing jobdesk, cutting objects, sticking, and colouring the blank media parts. The cooperation was carried out to speed up the time of montage work obtained based on aspects of coordinating skills, responsibility and contribution, communication, productivity.